2023
DOI: 10.3389/fgene.2023.1309069
|View full text |Cite
|
Sign up to set email alerts
|

Causal associations of sleep traits with cancer incidence and mortality

Shanshan Tian,
Longtao Huangfu,
Yanping Bao
et al.

Abstract: To explore the correlation and causality between multidimensional sleep traits and pan-cancer incidence and mortality among patients with cancer. The multivariable Cox regression, linear and nonlinear Mendelian randomization (MR), and survival curve analyses were conducted to assess the impacts of chronotype, sleep duration, and insomnia symptoms on pan-cancer risk (N = 326,417 from United Kingdom Biobank) and mortality (N = 23,956 from United Kingdom Biobank). In the Cox regression, we observed a linear and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…32 In a mendelian randomization study conducted in the UK Biobank Cohort, Tian et al reported a linear association between long sleep duration and all-cause mortality in cancer patients (OR, 5.56, 95% CI: 3.15-9.82, p = 3.42E-09), suggesting that as sleep duration increases so does risk of mortality in patients with cancer. 33 In our study, the greater cancer mortality risk observed among participants in the healthy-long trajectory is consistent with these previous findings. In sensitivity analyses, after excluding deaths within the first 2 years of follow-up, the long-healthy trajectory, but not the healthy-long, trajectory was associated with cancer mortality in fully adjusted models.…”
Section: Discussionsupporting
confidence: 93%
“…32 In a mendelian randomization study conducted in the UK Biobank Cohort, Tian et al reported a linear association between long sleep duration and all-cause mortality in cancer patients (OR, 5.56, 95% CI: 3.15-9.82, p = 3.42E-09), suggesting that as sleep duration increases so does risk of mortality in patients with cancer. 33 In our study, the greater cancer mortality risk observed among participants in the healthy-long trajectory is consistent with these previous findings. In sensitivity analyses, after excluding deaths within the first 2 years of follow-up, the long-healthy trajectory, but not the healthy-long, trajectory was associated with cancer mortality in fully adjusted models.…”
Section: Discussionsupporting
confidence: 93%